KOMUNIKASI PEMBERDAYAAN KELOMPOK PEDAGANG PANTAI PESONA (KP3) RUPAT UTARA OLEH DINAS KEBUDAYAAN, PARIWISATA, PEMUDA DAN OLAHRAGA KABUPATEN BENGKALIS - Widya Tri Andhini; Yasir " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Communication process is one of defining factor in the success of empowerment thecommunity. The planned program should distribute well. Therefore empowermentcommunication becomes a trend in managing the community to increase their standard ofliving especially for the community which far for receiving any information but still in the“circle” of extraordinary natural potential. The purpose of this research is to knowcommunication of empowerment, participation and obstacles happen to PantaiPesonaMerchant Group of North Rupat by Culture, Tourism, Youth and Sport Affair of BengkalisRegency.Model of the empowerment communication with democratic leadership has applied inthis research to measure the communication of empowerment. The research used qualitativemethod through descriptive analysis which refers to Huberman and Miles data modelsystematic analysis. Subject in this research are tanjung Medan’s headman, TanjungMedan’s Companion Village, and the members of PantaiPesona Merchants’ group (KP3)North Rupat.The result of this research indicates the efforts empowerment communication for thegroup development has run well. Generally, the patterns that showed up in thecommunication model above have been run well. It is just some sustaining success factors ofthis program not yet implemented maximally such as : the government hasn’t maximallyidentifying social community, the empowerment hasn’t done regularly and periodically, andthe parties involved in managing KP3RU hasn’t have good capacity and capability.Keywords: empowerment comunications, empowerment the community.